Pengaruh Penggunaan Kartu Kata Bergambar Terhadap Kemampuan Membaca Permulaan Siswa Sekolah Dasar - Chabib Towil Saputro (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
Based on the results of initial observations that have been carried out at SDN Pesanggrahan 01 Jakarta on August 29, 2023, it is stated that the reading ability of grade 1 students is still low, this is evidenced by the reading test conducted by the class 1A teacher at that time, namely there were 9 out of 23 students and class 1B there were 13 out of 23 students having difficulty in reading. Students find it difficult to understand the concept of letters and words, students also find it difficult to pronounce words and understand the content of reading. In its implementation, this study uses a type of experimental quantitative research through the provision of a special treatment / treatment in the experimental class. The type of True Experiment research was carried out with a Posttest only Group Design design. The sample in this study was taken using Probability sampling technique The results of the Normality Test using Kolmogorof-Smirnov showed that both data were normal. The results of the homogeneity test with a significance level of 0.05 or 5% after processing the data are significant. 0.471 <0.05 then the data is homogeneous. The results of the t-test in this study show that using an independent sample test with in the table it is known that the tcount value is 4.508, seen ttabel in the attached distribution is known ttabel = t0.5/2 (23+23-2) = t0.025 (44) = 1.1. then it is stated that tcount 4.508 > ttable 1.1 with a significance value of. 0.00 > 0.05. then ho is rejected ha is accepted so it can be concluded that there is an effect of picture word card media